Rabies, a global threat: taking science a step forward - Smith, Mylissia Rachelle (Kansas State University, 2014)
Rabies is the most deadly disease on earth and has a 99.9% human fatality rate. Rabies kills 61,000 humans annually and results in an economic burden of $124 billion USD annually. Each day 3.3 million people live with the risk of rabies. It is estimated that 95% of human rabies cases are a result of coming in contact with an infected canine, majority of these cases being children 15 years and younger. It is estimated that 1 person every 8 minutes dies of rabies. Rabies is a highly neurotropic disease which attacks the brain and central nervous system. Once clinical symptoms are presented, death is invariably the outcome as no cure exists for rabies. Rabies is 100% preventable in humans by proper wound management and proper administration of prophylaxis. Rabies can be adequately controlled in animal populations by contraception and animal rabies vaccine efforts. Whilst it is known that rabies can be prevented in humans and controlled in animal populations, further scientific efforts are still warranted to fully understand this deadly virus so that a cure can one day be discovered. As human and animal populations continue to grow, so does the cost and burden of this horrific disease. As a result, the importance of prophylaxis and passive immunity are critical in the event of medically managing an exposure, and preventing exposures. The World Health Organization has defined global recommendations for individuals and animals who have received prophylaxis to be adequately protected. Measuring this protection is performed using a variety of approved testing methodologies, virus-neutralizing assays and antigen-binding assays. Whilst the WHO recommendations were defined from clinical studies performed with virus-neutralizing assays, the assumption that these recommendations are suitable for the antigen-binding assays is inaccurate. The testing methodologies, virus-neutralization and antigen-binding, share similarities, as they are measuring an immune response to the rabies virus. However; enough differing characteristics are presented such that exact comparisons cannot be made. Establishing the same standards and recommendations for both testing methodologies will never be sufficient.
Keywords: Rabies; WHO recommendations; Lyssavirus; ELISA; Zoonosis; Canines; Animal Diseases (0476); Health Sciences (0566); Veterinary Medicine (0778)